KNOWLEDGE AND FLUID INTAKE MANAGEMENT LEAD MAINTENANCE DRY WEIGHT OF PATIENT UNDERGOING HEMODIALYSIS - Ace Sudrajat; Nelly Yardes; Tri Endah Pangastuti; Dewi Lusiani; Santa Manurung; Muhammad Syahrul Hajriyanto (Jurnal Keperawatan, 2025)
The incidence of end-stage renal disease in the worldwide. Approximately 70% (three million people worldwide) progress from renal failure to hemodialysis therapy. Renal failure is associated with a risk of fluid and electrolyte imbalance. Dry body weight is an indicator of adherence to fluid management, and the risk of complications prevents critical conditions. Risk of various complications, such as hypotension or hypertension, categories of knowledge, and lifestyle of fluid restriction. Knowledge of the relationship between knowledge and management of fluid intake retrieved from dry body weight hemodialysis patients. Quantitative Research with Cross-sectional Data Respondents and population comprised outpatients in the hemodialysis wards of the Jakarta Islamic Hospital Cempaka Putih zone in mid-year 2024. spearman rank statistical test knowledge with dry body weight p-value (0.004 <α0.05) correlation coefficient 0.328. fluid intake management, with a dry body weight p-value (0.009 <α0.05) correlation coefficient of 0.302. Conclusion: There was a significant relationship between knowledge and fluid intake management and dry body weight of hemodialysis patients. Future researchers should explore factors that can affect dry body weight.